2017
DOI: 10.1371/journal.pone.0177707
|View full text |Cite
|
Sign up to set email alerts
|

Working memory training in healthy young adults: Support for the null from a randomized comparison to active and passive control groups

Abstract: Training of working memory as a method of increasing working memory capacity and fluid intelligence has received much attention in recent years. This burgeoning field remains highly controversial with empirically-backed disagreements at all levels of evidence, including individual studies, systematic reviews, and even meta-analyses. The current study investigated the effect of a randomized six week online working memory intervention on untrained cognitive abilities in a community-recruited sample of healthy yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 92 publications
(120 reference statements)
0
22
0
Order By: Relevance
“…Hence, BFs allow for evaluating the strength of evidence not only for the presence of an association, but explicitly also for the absence of a proposed association. Accordingly, using BFs has become increasingly popular in the area of cognitive enhancement (e.g., Antón et al 2014;Clark et al 2017;De Simoni and von Bastian 2017;Guye and von Bastian 2017;Kirk et al 2014;Paap et al 2014;Sprenger et al 2013;von Bastian et al 2017;von Bastian and Oberauer 2013).Based on previous findings, we expected positive associations of motivation (Brose et al 2012), a growth mindset (Jaeggi et al 2014), and conscientiousness (Studer-Luethi et al 2012) with change in training performance. Regarding neuroticism, our expectations were less specific, given that previous literature reported evidence for a negative association of neuroticism with mean training performance and transfer effects, but not with training gains (e.g., Studer-Luethi et al 2012, 2016.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Hence, BFs allow for evaluating the strength of evidence not only for the presence of an association, but explicitly also for the absence of a proposed association. Accordingly, using BFs has become increasingly popular in the area of cognitive enhancement (e.g., Antón et al 2014;Clark et al 2017;De Simoni and von Bastian 2017;Guye and von Bastian 2017;Kirk et al 2014;Paap et al 2014;Sprenger et al 2013;von Bastian et al 2017;von Bastian and Oberauer 2013).Based on previous findings, we expected positive associations of motivation (Brose et al 2012), a growth mindset (Jaeggi et al 2014), and conscientiousness (Studer-Luethi et al 2012) with change in training performance. Regarding neuroticism, our expectations were less specific, given that previous literature reported evidence for a negative association of neuroticism with mean training performance and transfer effects, but not with training gains (e.g., Studer-Luethi et al 2012, 2016.…”
mentioning
confidence: 76%
“…Hence, BFs allow for evaluating the strength of evidence not only for the presence of an association, but explicitly also for the absence of a proposed association. Accordingly, using BFs has become increasingly popular in the area of cognitive enhancement (e.g., Antón et al 2014;Clark et al 2017;De Simoni and von Bastian 2017;Guye and von Bastian 2017;Kirk et al 2014;Paap et al 2014;Sprenger et al 2013;von Bastian et al 2017;von Bastian and Oberauer 2013).…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, there is no agreement because, whereas some studies have reported near and far transfer effects [8][9][10] , others have only found near transfer effects [11][12][13][14] , and still others did not find any kind of transfer [15][16][17][18] . At least five meta-analyses 5,7,[19][20][21] have been conducted to clarify the possible transfer effects in the working memory domain, but the overall results have been inconclusive.…”
mentioning
confidence: 95%
“…Eight outliers (3.8%) were removed (z NoResp ≥ 4 and z Hits ≥ 2.5) from the data set, in which participants completed two sessions (N = 213). Descriptive statistics for the performance on different versions of UCMRT at two time points are presented in & Perrig, 2017), and some even reporting worse performance in the second session than in the first (Clark, Lawlor-Savage, & Goghari, 2017;Colom et al, 2013;Redick et al, 2013;Stough et al, 2011). On the other hand, significant changes in performance in the two sessions were observed as a function of group (Table 2).…”
Section: Test-retestmentioning
confidence: 99%